Low glycaemic state increases risk of frailty and functional decline in older people with type 2 diabetes mellitus – Evidence from a systematic review. (November 2021) - Abdelhafiz, A.H.; Peters, S.; Sinclair, A.J.
Abstract: Aims: To explore risk of frailty and functional decline associated with low glycaemia in older people with type 2 diabetes. Methods: Systematic review. Results: 11 studies included. Six studies investigated risk of frailty or physical decline with hypoglycaemia. Hypoglycaemia increased risk of incident frailty (HR 1.60, 95% CI 1.14 to 2.42) in one study and risk of fractures in four studies (2.24, 1.56 to 3.21, 1.24, 1.13 to 1.37, 1.94, 1.67 to 2.24 and 1.71, 1.35 to 2.16 respectively). In sixth study, hypoglycaemia associated with dependency (P < 0.001). Five studies explored association of low blood glucose/HbA1c with frailty. One study showed that mean blood glucose decreased with increasing frailty (p = 0.003). Two studies reported that HbA1c inversely correlated with clinical frailty scale (r = -0.31, p < 0.01) and HbA1c < 6.9% increased risk of frailty (HR, 1.41 95% CI 1.12 to 1.78) respectively. Last two studies showed that HbA1c < 6.5% associated with risk of any fracture (HR 1.08, 95% CI 1.06 to 1.11) and HbA1c < 6.0% associated with increased risk of care need (3.45, 1.02 to 11.6) respectively. Conclusions: Low glycaemia increases risk of frailty and functional decline in older people with type 2 diabetes. Management should minimise incidence of low glycaemia in these patients.